A survey of library equipments in academic libraries in Ibadan, Oyo State (2012)
This study investigated the availability of library and equipment tools used in selected academic libraries in Ibadan, Nigeria. A structured questionnaire was developed to elicit information from the personnel of the selected libraries on the equipments and tools available in their respective libraries. The data were collated, analyzed and interpreted based on standard statistical method. The results of the study revealed that equipment in academic libraries in Ibadan were grossly inadequate for processing and information services, that the relationship between libraries size and equipments available in academic libraries is not statistically significant and that staff output is affected by equipment availability. This was found to be as a result of inadequate funding, poor infrastructural facilities and more attention given to ICT facilities by most of the libraries. Based on the outcome of the study, it was recommended that adequate funds be made available to the libraries to procure library equipment on regular basis and that staff productivity be enhanced by adequate provisions of tools and equipment.